Drivers’ Readiness To Use Car Driving Simulator As A Tool To Improve Driving Skill: A Preliminary Study - Rozmi, Ismail; Mohamad Hanif, Md Saad; Mohd Jailani, Mohd Nor; Redzwan, Rosli (Penerbit UTM Press, 2016)
Driving simulators have existed since the 1960s, but for a long time they remained too expensive to be used widely for training purposes. As IT related technology improved, the cost of driving simulators goes down in the last few years. Today, driving simulators have been used as a training device in the basic driver training. In developed countries the use of simulator in driving education is not new. In Malaysia, however, the use of simulators in training is quite new compared to other Asian countries. This paper presents the results of preliminary study on the readiness of Malaysian driver to use car driving simulator in training and education prior to driver licensing. Survey method was used to get information on drivers’ perception toward the introduction of driving simulator in selected driving institutes. The results of this study showed that all respondents agreed on the importance and usefulness of the driving simulator in improving the driving training process. Based on the result of this study, it is suggested that driving simulator should be implemented in the driving curriculum in order to produce competent driver.